2012
DOI: 10.1007/s00417-011-1903-6
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone attenuates activation of human Tenon’s fibroblasts induced by transforming growth factor -β1

Abstract: Rosiglitazone can effectively attenuate activation of HTFs induced by TGF-β1 without obvious toxicity. The possible mechanism might be that rosiglitazone interferes with TGF-β/Smad signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Rosiglitazone is known for its ability to improve insulin sensitivity and has been used extensively in patients with non-insulin-dependent diabetes mellitus. However, rosiglitazone has been proven to have an anti-fibrotic effect in multiple organs [24][26], and we previously demonstrated that rosiglitazone exerts its anti-fibrotic effect through suppression of Smad2/3 [12]. In this study, we investigated the effect of rosiglitazone on the p38 signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Rosiglitazone is known for its ability to improve insulin sensitivity and has been used extensively in patients with non-insulin-dependent diabetes mellitus. However, rosiglitazone has been proven to have an anti-fibrotic effect in multiple organs [24][26], and we previously demonstrated that rosiglitazone exerts its anti-fibrotic effect through suppression of Smad2/3 [12]. In this study, we investigated the effect of rosiglitazone on the p38 signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Human Tenon fibroblasts were seeded in six-well plates, and scratch wounds were induced as described previously [12]. After suspended particles were washed away, we pretreated the cells with rosiglitazone for 2 h or SB203580 for 1 h in serum-starved medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…troglitazone, rosiglitazone, and pioglitazone) have anti-fibrogenic effect in several body tissues, including the lungs, skin, kidneys, eyes and heart [2635]. The PPAR-γ agonists inhibit fibrogenesis by regulating the Smad-dependent [27, 3033] or Smad-independent [23, 29, 31, 36] TGF-β signaling pathways. The mechanism of anti-fibrotic action of PPAR-γ agonists is under investigation but involves both PPAR-γ dependent [26, 32, 37, 38] and PPAR-γ independent [28, 31, 3436] pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It may also suppress invasion of macrophages into the healing subconjunctival tissue and generation of myofibroblasts [51]. Consistent with this result, Fan [52] and his fellows reported that rosiglitazone can effectively attenuate activation of human Tenon's fibroblasts (HTFs) induced by TGF β 1 without obvious toxicity. The possible mechanism might be that rosiglitazone interferes with TGF β /Smad signaling pathway.…”
Section: Ppar γ and Ocular Diseasementioning
confidence: 82%